Benchmarking working conditions for health and safety in the frontline healthcare industry: Perspectives from Australia and Malaysia - McLinton, Sarven Savia; Loh, May Young; Dollard, Maureen Frances; Tuckey, Michelle M.R.; Idris, Mohd Awang; Morton, Sharon (Wiley, 2018)
Aim: To present benchmarks for working conditions in healthcare industries as an initial effort into international surveillance. Background: The healthcare industry is fundamental to sustaining the health of Australians, yet it is under immense pressure. Budgets are limited, demands are increasing as are workplace injuries and all of these factors compromise patient care. Urgent attention is needed to reduce strains on workers and costs in health care, however, little work has been done to benchmark psychosocial factors in healthcare working conditions in the Asia-Pacific. Intercultural comparisons are important to provide an evidence base for public policy. Design: A cross-sectional design was used (like other studies of prevalence), including a mixed-methods approach with qualitative interviews to better contextualize the results. Methods: Data on psychosocial factors and other work variables were collected from healthcare workers in three hospitals in Australia (N = 1,258) and Malaysia (N = 1,125). 2015 benchmarks were calculated for each variable and comparison was conducted via independent samples t tests. Healthcare samples were also compared with benchmarks for non-healthcare general working populations from their respective countries: Australia (N = 973) and Malaysia (N = 225). Findings: Our study benchmarks healthcare working conditions in Australia and Malaysia against the general working population, identifying trends that indicate the industry is in need of intervention strategies and job redesign initiatives that better support psychological health and safety. Conclusion: We move toward a better understanding of the precursors of psychosocial safety climate in a broader context, including similarities and differences between Australia and Malaysia in national culture, government occupational health and safety policies and top-level management practices.